De l’anthropologie en général à l’anthropologie du Maghreb - Marouf, Nadir (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
Anthropologyis a specialtywhosebounderies have always been ambiguous and whose directions has not ceased to change by takingintoconsideration : the context, the taste of the times and ideologies. It has a history of the following stages: 1/Romantic 2/Cantonesebased on the heritage of Aristotle 3/Durkheimia 4/Colonial 5/Postcolonialism. It wasdominated by 3 main orientations produced by 3 schools: French, English and American. As for Algeria in this last stage, the networks of analysiscrossedfrom structural, functional and pervasive, and therewas a contextthatcaused the displacement of the researchfrom the former colonial country to the colonised country. The researchalsosought to address the folklore phenomenon for the purpose of valuing the heritage and took the official position thatthereis no place except for social sciences whichcontribute to national construction and development and consideredanthropology to be colonial. The new data of the national state, the emerging bourgeoisie, the economies of developing countries and  services have become distinctive subjects of the study of anthropology.